Kualitas diet berhubungan dengan defisiensi besi pada atlet remaja putri - Fillah Fithra Dieny; Ria Fitri Setyaningsih; A Fahmy Arif Tsani (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
An adolescent female athlete has a high risk of suffering iron deficiency. Low-quality diets reflect a lack of variety, adequacy, balance, and moderation, but these have not been associated with iron deficiency. This study aimed to analyze the relationship of diet quality with iron deficiency. Methods, the research was conducted at the Student Center for Education and Sports Training Central Java, the Salatiga athletic club, the Semarang State University athletic, and the swimming club. The subjects were 82 female athletes aged 13-21 years who were selected by purposive sampling. The variables of this study were diet quality and iron deficiency. The diet quality measured by assessing food consumption used the Semi-Quantitative Food Frequency Questionnaire and then the diet quality score calculated by Diet Quality Index-International. Iron deficiency measured based on serum ferritin level. The bivariate was analyzed by the Rank Spearman test. Results, as many as 17,1% of subjects suffering iron deficiency and 95,1% of subjects had low diet quality. Diet quality and its component; Variety, adequacy, moderation, and overall balance were associated with serum ferritin (p<0,05). Energy, protein, iron, fiber adequacy also related to serum ferritin, but vitamin C adequacy was not related to this. In conclusion, low-quality diets are associated with iron deficiency in female athletes.